Genetic Differences in Human Circadian Clock Genes among Worldwide Populations - Ciarleglio, Christopher M; Ryckman, Kelli K; Servick, Stein V; Hida, Akiko; Robbins, Sam; Wells, Nancy; Hicks, Jennifer; Larson, Sydney A; Wiedermann, Joshua P; Carver, Krista; Hamilton, Nalo; Kidd, Kenneth K; et al. (Journal of biological rhythms, 2008)
The daily biological clock regulates the timing of sleep and physiological processes that are of fundamental importance to human health, performance, and well-being. Environmental parameters of relevance to biological clocks include (1) daily fluctuations in light intensity and temperature, and (2) seasonal changes in photoperiod (day length) and temperature; these parameters vary dramatically as a function of latitude and locale. In wide-ranging species other than humans, natural selection has genetically optimized adaptiveness along latitudinal clines. Is there evidence for selection of clock gene alleles along latitudinal/photoperiod clines in humans? A number of polymorphisms in the human clock genes Per2, Per3, Clock, and AANAT have been reported as alleles that could be subject to selection. In addition, this investigation discovered several novel polymorphisms in the human Arntl and Arntl2 genes that may have functional impact upon the expression of these clock transcriptional factors. The frequency distribution of these clock gene polymorphisms is reported for diverse populations of African Americans, European Americans, Ghanaians, Han Chinese, and Papua New Guineans (including 5 subpopulations within Papua New Guinea). There are significant differences in the frequency distribution of clock gene alleles among these populations. Population genetic analyses indicate that these differences are likely to arise from genetic drift rather than from natural selection.